Foundations of credibility. - Tan, Vincent Chee Sum. (2012)
Detective fictions need foundations of credibility to be believable and thus enjoyable. The foundations begin with the narrative frame, from which the crime, the criminal, the detective, are built. Each new addition depends on the credibility of the foregoing for its credibility. Structurally, the solution depends on the crime and detective, which depend on the narrative frame. I examine a portion of "A Study in Scarlet", contrasting it with the beginning of "Monsieur Lecoq" to demonstrate this dependency, and the importance of foundations of credibility in detective fiction.